THE PRINCIPLES OF ISLAMIC GUIDANCE AND COUNSELING IN MENTAL DEVELOPMENT ACTIVITIES IN THE STATE POLICE SCHOOL OF THE NORTH SUMATERA REGIONAL POLICE - Siti Asiyah; Saipul Achyar; Abdurrahman Abdurrahman (Conciencia, 2020)
This research was conducted preceded by the desire of the researcher himself to explore the principles of counseling guidance at the State Police School (SPN) of the North Sumatra Regional Police. This study aims to determine the role of Guidance and Counseling in Mental Development activities at the North Sumatra Regional Police State Police School. The method used in writing this research was qualitative in a case study approach. The research data were collected through interviews and observations. Furthermore, the data were analyzed using thematic analysis techniques. The results showed that in terms of motivating the State Police School students to apply the principles of Islamic guidance and counseling, so as to achieve good learning outcomes and mentally healthy. This can be seen from the success of these students in completing the learning process. Furthermore, the mental assessment of students in terms of problems that did students have restrictions and obligations. If you violated the prohibition, you will be mentally reduced. Personality mentality reflected in student learning outcomes, so if the student's mentality was good then the performance will be good.